STOCHASTIC POROSITY MODELING IN VOLCANIC RESERVOIR JATIBARANG FORMATION - Eko Widianto; Firman Herdiansyah; Muhammad Burhannudinnur; Suryo Prakoso; Benyamin Benyamin (Journal of Geoscience Engineering & Energy (JOGEE), 2021)
Jatibarang Formation known as interesting volcanic reservoir in North West Java Basin. The reservoir was characterized by altered and naturally fractured that has significantly producing light oil. The volcanic Jatibarang reservoir consist of 3 volcanic cycles that are cycle 1, cycle 2 and cycle 3 with 16 faults configuration. Total and Fracture porosity modeling was conducted to determine secondary porosity distribution using stochastic method. Lithofacies and property lateral variation were generated to visualize geological model. Total porosity was estimated using formation evaluation. Natural subsurface fracture has been identified by bore hole image (formation micro imager) and geophysical log from several wells in the Jatibarang Field. It has provided both lithology and property reservoir information. Lithofacies tuff and non tuff model has been used as a constrait to distribute pore pressure and bulk modulus. Then, porosity model was distribution using the collocated-co kriging method. The purpose of this study was to determine the distribution of total and fracture porosity of the Jatibarang volcanic reservoir.